Characterization of Olfactory Ensheathing Glial Cells Cultured on Polyurethane/Polylactide Electrospun Nonwovens. (31st March 2015) - Grzesiak, Jakub; Fryczkowski, Ryszard; Lis, Anna; Szarek, Dariusz; Laska, Jadwiga; Marycz, Krzysztof
Abstract : The aim of this research was to evaluate novel biomaterials for neural regeneration. The investigated materials were composed of polyurethane (PU) and polylactide (PLDL) blended at three different w/w ratios, that is, 5/5, 6/4, and 8/2 of PU/PLDL. Ultrathin fibrous scaffolds were prepared using electrospinning. The scaffolds were investigated for their applicability for nerve regeneration by culturing rat olfactory ensheathing glial cells. Cells were cultured on the materials for seven days, during which cellular morphology, phenotype, and metabolic activity were analysed. SEM analysis of the fabricated fibrous scaffolds showed fibers of a diameter mainly lower than 600 μ m with unimportant volume of protrusions situated along the fibers, with nonsignificant differences between all analysed materials. Cells cultured on the materials showed differences in their morphology and metabolic activity, depending on the blend composition. The most proper morphology, with numerous p75 + and GFAP + cells present, was observed in the sample 6/4, whereas the highest metabolic activity was measured in the sample 5/5. However, none of the investigated samples showed cytotoxicity or negatively influenced cellular morphology. Therefore, the novel electrospun fibrous materials may be considered for regenerative medicine applications, and especially when contacting with highly sensitive nervous cells.